LRST model movable trevis: A novel method to restrain cattle in barns - C, IBRAHEEM KUTTY; B, BIBIN BECHA; T, VENKATACHALAPATHY R; C P, ABDUL AZEEZ (The Indian Journal of Animal Sciences, 2021)
Appropriate and humane method of restraining the animals is essential to perform any type of clinical examination especially during the use of modern diagnostic equipments like ultrasound scanner. Procedures involving repeated screening of more number of animals make it difficult to move them for restraining in fixed facilities like chute/trevis outside the barn. The ongoing research project on impact of thermal stress on fertility of cows involve ultrasound scanning, blood collection and other observations on many cows almost every day over a period of one year and necessitate repeated restraining. Hence, the idea of fabricating a convenient movable trevis to restrain cows within the barns was initiated and the final device developed through step by step improvisation was named as LRST model trevis. The trevis could be rolled within the barn to enclose the animal in its standing space and was fixed in situ using the facilities provided. The removable metal tray was used for placing the ultrasound scanner/other equipments in a safe and convenient position. The trevis on wheels was found to be very useful for transrectal ultrasound scanning and other procedures as it causes minimum stress to the animal, comfortable for the examiner, trouble free for the helpers, ensures safety and cleanliness of the machine, time saving and facilitates more effective diagnostic intervention. Hence, the LRST model movable trevis can be adopted with minor changes to suit individual farms for convenient handling and clinical examination especially ultrasound scanning of large ruminants within the barns.